Optimizing Healthcare Performance Through Electronic Medical Records: An Efficiency Analysis - Purniari, Ni Kadek Tika; Nilna Muna (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2024)
Burnout among healthcare workers has become a significant issue in the medical field, partially due to the adaptation process to Electronic Medical Records (EMR). While EMR technology is designed to enhance efficiency and accuracy in patient care, it often poses challenges during implementation. This study aims to examine the impact of medical record digitalization on healthcare worker performance, mediated by high-quality data access and data-driven decision-making at Wangaya Regional Hospital. Using the SEM-PLS method and involving 244 healthcare workers, the research reveals that medical record digitalization significantly improves data access and data-driven decision-making. The findings indicate that EMR plays a crucial role in enhancing healthcare worker performance by facilitating quicker, more accurate, and up-to-date information access, ultimately improving service efficiency and effectiveness. These results support the implementation of digital transformation in medical record management to improve healthcare worker performance and, consequently, the overall quality of healthcare services